THE ROLE OF TECHNOPRENEURSHIP IN REDUCING UNEMPLOYMENT IN INDONESIA - M. Ikmal Husein Lubis; Ritha F. Dalimunthe; Prihatin Lumbanraja (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The condition of unemployment today is not synonymous with uneducated people, hundreds of thousands of graduates are still unemployed, of course this is a problem that must find a solution. In the current era of technological development, it should be able to encourage the creation of new innovations and discoveries that have economic value. The development of technology-based entrepreneurship can have a positive impact on society at large. This research aims to provide a new perspective on technopreneurship in reducing unemployment in Indonesia and provide evaluation material to stakeholders so that entrepreneurial technopreneurship can contribute to the progress of Indonesia's development. The method used in the process of writing this article is to use a literature review technique. The results of this research are that the role of technopreneurship is very important, including: (1) Technopreneurship participates in the development of the country by increasing the economic level of society, (2) Technopreneurship is able to utilize technology. which is increasingly sophisticated, (3) Technopreneurship as a solution in reducing unemployment rates, (4) Technopreneurship is the latest innovation in sustainable business development so it needs to be developed by young people and Indonesian society.